2017
DOI: 10.1002/ana.25020
|View full text |Cite
|
Sign up to set email alerts
|

Cortical pathology in multiple sclerosis detected by the T1/T2‐weighted ratio from routine magnetic resonance imaging

Abstract: ObjectiveIn multiple sclerosis, neuropathological studies have shown widespread changes in the cerebral cortex. In vivo imaging is critical, because the histopathological substrate of most measurements is unknown.MethodsUsing a novel magnetic resonance imaging analysis technique, based on the ratio of T1‐ and T2‐weighted signal intensities, we studied the cerebral cortex of a large cohort of patients in early stages of multiple sclerosis. A total of 168 patients with clinically isolated syndrome or relapsing–r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
120
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 45 publications
5
120
1
Order By: Relevance
“…Previous studies have suggested that myelin is the predominant source of MR contrast in T1‐weighted and T2‐weighted images (Bock, Kocharyan, Liu, & Silva, ; Eickhoff et al, ; Laule et al, ; Wallace et al, ), and by using the ratio of these images the contrast sensitivity to detect myelin content is increased further due to attenuation of the shared intensity biases (Glasser & Van Essen, ). Although, other studies have questioned the sensitivity of the T1‐w/T2‐w ratio for myelin content, and argued that it is likely not the only factor contributing to the T1‐w/T2‐w image (Arshad et al, ; Righart et al, ; Uddin et al, ). Still, it has been shown that T1‐w/T2‐w ratio differentiates between high and low myelinated cortex as determined by myelin proteolipid protein staining (Nakamura et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that myelin is the predominant source of MR contrast in T1‐weighted and T2‐weighted images (Bock, Kocharyan, Liu, & Silva, ; Eickhoff et al, ; Laule et al, ; Wallace et al, ), and by using the ratio of these images the contrast sensitivity to detect myelin content is increased further due to attenuation of the shared intensity biases (Glasser & Van Essen, ). Although, other studies have questioned the sensitivity of the T1‐w/T2‐w ratio for myelin content, and argued that it is likely not the only factor contributing to the T1‐w/T2‐w image (Arshad et al, ; Righart et al, ; Uddin et al, ). Still, it has been shown that T1‐w/T2‐w ratio differentiates between high and low myelinated cortex as determined by myelin proteolipid protein staining (Nakamura et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear what biological substrate higher T1‐w/T2‐w values reflect. Disorders with a strong demyelinating component such as MS, have consistently showed lower T1‐w/T2‐w values in pathologically vulnerable regions (Beer et al, ; Nakamura et al, ; Righart et al, ). Additionally, lowered T1‐w/T2‐w ratios in several brain regions in schizophrenia (Ganzetti et al, ; Iwatani et al, ) and bipolar disorder patients (Ishida et al, ) have been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5, 9, 37 A recent MRI-pathology study has linked the T1w/T2w ratio to dendrite density but not myelin content. 22 Thus, the T1w/T2w ratio in the midbrain may reflect a sum of multiple PD-related changes involving neurons, dendrites, microglia, and iron content. This information might generate a more potent contrast that may be superior to other MRI sequences in capturing PD-related pathology and can be used as a biomarker for PD early detection.…”
Section: Discussionmentioning
confidence: 99%
“…Originally proposed by Glasser et al, 19 a simple division of these images can yield a new quantitative contrast (T1w/T2w ratio) with high spatial resolution, test-retest reliability, and sensitivity to neurodegenerative changes demonstrated by recent studies. 2022 Its simplicity and broad availability make it a promising candidate for studying PD-related changes. To our knowledge, there is neither a study that has used the T1w/T2w ratio to study structures other than cortical regions, nor has it been applied yet to a PD population.…”
Section: Introductionmentioning
confidence: 99%